Case Report: ISG15 deficiency caused by novel variants in two families and effective treatment with Janus kinase inhibition - Burleigh, Alice; Moraitis, Elena; Al Masroori, Eman; Al-Abadi, Eslam; Hong, Ying; Omoyinmi, Ebun; Titheradge, Hannah; Stals, Karen; Jones, Wendy D.; Gait, Anthony; Jayarajan, Vignesh; Di, Wei-Li; et al. (Frontiers in Immunology, 2023)
ISG15 deficiency is a rare disease caused by autosomal recessive variants in the ISG15 gene, which encodes the ISG15 protein. The ISG15 protein plays a dual role in both the type I and II interferon (IFN) immune pathways. Extracellularly, the ISG15 protein is essential for IFN-γ-dependent anti-mycobacterial immunity, while intracellularly, ISG15 is necessary for USP18-mediated downregulation of IFN-α/β signalling. Due to this dual role, ISG15 deficiency can present with various clinical phenotypes, ranging from susceptibility to mycobacterial infection to autoinflammation characterised by necrotising skin lesions, intracerebral calcification, and pulmonary involvement. In this report, we describe novel variants found in two different families that result in complete ISG15 deficiency and severe skin ulceration. Whole exome sequencing identified a heterozygous missense p.Q16X ISG15 variant and a heterozygous multigene 1p36.33 deletion in the proband from the first family. In the second family, a homozygous total ISG15 gene deletion was detected in two siblings. We also conducted further analysis, including characterisation of cytokine dysregulation, interferon-stimulated gene expression, and p-STAT1 activation in lymphocytes and lesional tissue. Finally, we demonstrate the complete and rapid resolution of clinical symptoms associated with ISG15 deficiency in one sibling from the second family following treatment with the Janus kinase (JAK) inhibitor baricitinib.